Religious leaders perspective on the effects of ‘hitting the bottle hard’ amongst the youth in Musina Town, Limpopo province - Matlakala, Frans Koketso; Makhubele, Jabulani Calvin; Hasheela, Miriam Winnie; Ananias, Janetta Agnes; Rapholo, Selelo Frank; Anesu, Svinurai; Namoonga, Chilwalo Beatrice; Prudence, Mafa; Freeman, Rachel Johanna; Ilonga, Hamuse Tiberia Ndanyakuwa (Penerbit Universiti Kebangsaan Malaysia, 2019)
Binge drinking has enormous effects on the youth and the hardships reverberates beyond an individual, felt by family and community at large. There are numerous effects that are associated with excessive drinking including, risky sexual behaviour, increased risk of sexual transmitted diseases and socio-economic challenges. Therefore, this study aimed as exploring and describing the effects of hitting the bottle hard amongst the youth in Musina Town in Limpopo province. The researchers used qualitative research approach to explore the effects of alcohol abuse. The type of research used was a mixture of exploratory and descriptive in nature. In particular, multiple case study design was used. The study constituted of church leaders and they were purposively chosen because they are custodians of moral values and conducts which abhor excessive use of alcohol within their communities. Besides purposeful chosen, their availability and convenience were considered. Data was collected through structured interviews and thematic data analysis method was used. Ecosystems theory was used to guide the study. It was discovered that those who hit the bottle hard are at risk of unsafe sexual intercourse, workplace absenteeism and neglect their family responsibility and involve themselves in unlawful acts. As such, the study conclude that youth experience tremendous effects after they intoxicate themselves and therefore, this study recommends that the programmes and services targeting young people should be developed and be contextualised as per their needs.